Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1530-0277.2006.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Characteristics of Children with Fetal Alcohol Spectrum Disorders in Communities from Italy: Preliminary Results

Abstract: This research indicates that a nonclinic-referred sample of Italian children with FASD display a profile of neurobehavioral functioning consistent with that reported by other researchers. Furthermore, the neurobehavioral characteristic most identified with children diagnosed with FASD was inattention followed by hyperactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 49 publications
5
45
0
3
Order By: Relevance
“…5,9 One approach used successfully to determine the minimal prevalence of FASD in communities in South Africa, [10][11][12][13][14] Italy, 15,16 and Croatia 17,18 uses active case ascertainment in schools. Providing targeted physical examinations and cognitive/ behavioral testing to primary school children [19][20][21][22] and interviewing their mothers [23][24][25] can be effective for studying FASD prevalence and characteristics.…”
mentioning
confidence: 99%
“…5,9 One approach used successfully to determine the minimal prevalence of FASD in communities in South Africa, [10][11][12][13][14] Italy, 15,16 and Croatia 17,18 uses active case ascertainment in schools. Providing targeted physical examinations and cognitive/ behavioral testing to primary school children [19][20][21][22] and interviewing their mothers [23][24][25] can be effective for studying FASD prevalence and characteristics.…”
mentioning
confidence: 99%
“…Quanto às habilidades de leitura e escrita, este trabalho evidenciou que ambos os sujeitos apresentaram alterações signifi cativas, sendo estas prejudiciais ao processo de aprendizagem da leitura e da escrita. Alguns estudos publicados na área também encontraram difi culdades quanto ao desempenho das habilidades acadêmicas nos portadores da SAF 28,31 . O ITPA permitiu que a avaliação fonoaudiológica fosse complementada a partir do perfi l de habilidades psicolingüísticas, o qual também só pôde ser obtido pelo desempenho do S2, uma vez que o S1 não atingiu escore base para continuidade da aplicação dos subtestes.…”
Section: Discussionunclassified
“…Várias pesquisas comprovaram a presença de difi culdades de memória, envolvendo prejuízos tanto no armazenamento quanto na evocação da informação verbal, o que justifi caria as difi culdades na aprendizagem global desses indivíduos 12,13,24,25 , incluindo o aprendizado de conceitos lógico-matemáticos e também sócio-comunicativos [26][27][28] . O tempo aumentado para o processamento da informação 29,30 , somado a difi culdade de atenção e o comportamento hiperativo/impulsivo, sugere ser um dos principais fatores relacionados à difi culdade de aprendizagem desses indivíduos 31 . No Brasil, ainda são escassas pesquisas direcionadas a investigação do perfi l de habilidades de linguagem em pacientes com SAF.…”
Section: Aspectos Audiológicos Cognitivos E Lingüísticos Na Safunclassified
“…Uncertainty exists regarding the exact relationship of FAS to FASD globally which may result from: differing methodology used in case ascertainment; a study focus on FAS versus FASD (May et al, 2009); the sensitivity and specificity of diagnostic tools used (Kodituwakku et al, 2006) as well as differences in the profiles of co-morbid risk factors in the participants studied (May et al, 2009). However, what remains clear is that South Africa is the world leader in the rates of FAS or FASD.…”
Section: Identification Of Gaps or Needs For Further Researchmentioning
confidence: 97%
“…possibly because diagnosing the more severe end of the spectrum of disorders is much easier, thus under diagnosing the full spectrum of the disorder. More recently it has been found that in some studies increasing numbers of PFAS compared to FAS children have been identified as a result of more sensitive and specific tests being applied to children with FASD (Kodituwakku et al, 2006). Furthermore, May and colleagues, 2009, believe that in South Africa the ratio of FAS to FASD is much higher due to the high levels of maternal risk factors such as low socio-economic status and binge drinking in the communities studied.…”
Section: U N I V E R S I T Y O F C a P E T O W N 43mentioning
confidence: 99%